«O res mirabilis»: Spunti per una ripresa del carattere reale della presenza di Cristo nell'Eucaristia - Pagazzi, Giovanni Cesare (Teologia, 2021)
In some texts of sacramental theology and liturgy, in dealing with the type of presence of Christ in the Eucharist, there is a certain uneasiness in resorting to terminology pertaining to the sphere of "reality". Perhaps because one fears the risk of qualifying the presence in a cosifying and static way, disrespectful of the unrepeatable story of the Son of God in the world, without regard for the dynamism of the liturgical action and the effective contribution of the celebrating community and of the individual faithful in the realisation of the meaning of what happens. If such concerns are understandable and well-founded, the question remains whether they do not imply an understanding that is, to say the least, naive of the mystery of things, of realities. Starting from a renewed phenomenology of things, the essay proposes an understanding of the real and realistic dimension of the presence of the Lord in the Eucharist, capable of grasping the human and theological meaning of this presence, without bypassing the aspect real (res), but rather finding in this aspect one of its starting points. (English)